(untitled) (World Bulletin of Public Health, 2026)
Rising obesity and insulin resistance in young adults threaten longterm cardiovascular health. We examined how these metabolic factors relate to 24-hour blood pressure variability (BPV) and occupational performance in 180 healthy young soldiers (mean age 22 years). Participants underwent clinical assessment (BMI, waist circumference), 24-h ambulatory BP monitoring (ABPM) including mean daytime/nighttime BP, dipping status, morning surge and BP variability indices, and laboratory testing (lipid profile, fasting glucose, insulin for HOMA-IR, HbA1c, cortisol, vitamin D, magnesium, liver enzymes, CBC). We also recorded 12-lead ECG and echocardiography, and collected functional performance data (physical fitness tests, service readiness measures). Overweight/obese subjects (n=60) had significantly higher HOMA-IR and dyslipidemia than controls (all p